Potensi The Ogoh-Ogoh Bali Collection Sebagai Atraksi Wisata Budaya Di Desa Mengwi Kabupaten Badung - I Wayan Nanendra Dama Gunawan; I Made Bayu Ariwangsa (JURNAL DESTINASI PARIWISATA, 2017)
The Ogoh-ogoh Bali Collection is a center place to preserve one of the Balinese traditions that is "Ogoh-Ogoh", which is also seen as a small monument to preserve the culture as well as supporting tourism, especially cultural tourism. The Ogoh-Ogoh Bali Collection is located in Mengwi village, Badung regency, which has the great potential of cultural tourism in the form of cultural collections and interesting attraction for tourists. Based on these assumptions the background study of the topic chosen has raised concerns about the potential The Ogoh-Ogoh Bali Collection and obstacles faced in the management of cultural tourism attractions. Types and sources of data used are qualitative, primary and secondary data. Data collection is conducted by observation, interview, documentation, literature study, research instrument in the form of guide lines for the interview. Analysis of the data used is descriptive qualitative data analysis using a matrix approach to the concept of 4A and SWOT analysis. These results indicate that the potential of the Ogoh-Ogoh Bali is quite large, in addition to have a collection that contains the value of history,art and culture, and spiritual, The Ogoh-Ogoh Bali also has a show or attraction called "The Ogoh-Ogoh Dance". Although the potential of theOgoh-Ogoh Bali is quite large, but to date, there are still many experienced constraints that must be resolved. Thus, that the Vision and Mission of the program from the manager of TheOgoh-OgohBali can be implemented. Keywords: Potential, Ogoh-Ogoh,Tourist Attraction, Cultural Tourism